Synthesis and characterisation of organic-inorganic hybrid block copolymers of polydimethylsiloxane and polystyrene - Bayley, Gareth Michael (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.